Pelatihan Bahasa Inggris untuk Mendukung Daya Saing Internasional - Hernadi, Nour Ardiansyah; Sugiarto, Eko; Hakim, Lutfi Maulana (Penerbit Widina, Widina Media Utama, 2025)
Turgo-Merapi Tourism Village is a community-based destination located on the slopes of Mount Merapi, Sleman Regency, Yogyakarta Special Region. The village possesses substantial potential in terms of natural beauty, cultural richness, and local wisdom, which collectively contribute to its attractiveness for both domestic and international tourists. Nevertheless, the development of this destination continues to face several challenges, particularly the limited English language proficiency of local tour guides. This linguistic barrier hampers the provision of optimal services to international visitors, thereby necessitating capacity-building initiatives focused not only on physical infrastructure but also on human resource development. Proficiency in English is an essential competency for tour guides, functioning not merely as a communication tool but also as a medium to convey the uniqueness of the destination. Guides with adequate English skills are able to enrich the visitor experience, enhance the professional image of the destination, and expand the global tourism market reach. To address this critical need, a specialized English language training program was implemented for Turgo tour guides. The program encompassed structured stages, including theoretical input, role-play simulations, and field practice, enabling participants to apply language skills in authentic contexts. The training was facilitated by lecturers and undergraduate students of English studies, who acted as both instructors and mentors. The outcomes of the program indicated significant improvement in participants’ communication skills, motivation, and confidence in engaging with foreign tourists. In addition to acquiring new vocabulary, participants demonstrated the ability to construct appropriate responses to diverse tourist inquiries. More broadly, this initiative not only strengthened individual capacities but also contributed to the advancement of Turgo Tourism Village as a model of community-based tourism that is increasingly prepared to compete at the international level.ABSTRAKDesa Wisata Turgo-Merapi merupakan destinasi wisata berbasis masyarakat yang terletak di lereng Gunung Merapi, Kabupaten Sleman, Daerah Istimewa Yogyakarta. Desa ini memiliki potensi besar dari segi keindahan alam, kekayaan budaya, serta kearifan lokal yang mampu menarik wisatawan domestik maupun mancanegara. Namun, pengembangannya masih menghadapi sejumlah tantangan, terutama keterbatasan kemampuan bahasa Inggris pemandu wisata lokal. Hal ini menjadi kendala dalam memberikan layanan optimal kepada wisatawan asing sehingga diperlukan upaya peningkatan kualitas sumber daya manusia di samping penyediaan fasilitas pendukung. Kemampuan berbahasa Inggris merupakan keterampilan utama bagi pemandu wisata karena tidak hanya berfungsi sebagai alat komunikasi, tetapi juga sebagai sarana menyampaikan informasi mengenai keunikan destinasi. Pemandu dengan kemampuan bahasa yang baik dapat memberikan pengalaman lebih berkesan, meningkatkan citra profesional, serta memperluas jangkauan pasar pariwisata. Untuk menjawab kebutuhan tersebut, diselenggarakan program pelatihan bahasa Inggris khusus bagi pemandu wisata Desa Turgo. Program ini mencakup tahapan pembekalan materi, praktik dengan metode role-play, hingga praktik lapangan yang memungkinkan peserta berinteraksi langsung. Pelatihan difasilitasi oleh dosen dan mahasiswa Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta yang berperan sebagai narasumber sekaligus pendamping. Hasil program menunjukkan peningkatan signifikan pada keterampilan komunikasi, motivasi, dan rasa percaya diri peserta dalam melayani wisatawan asing. Mereka tidak hanya menambah kosakata baru, tetapi juga mampu melatih respons terhadap berbagai pertanyaan. Secara lebih luas, program ini tidak hanya memperkuat kapasitas individu, tetapi juga mendukung pengembangan Desa Wisata Turgo-Merapi sebagai destinasi unggulan berbasis masyarakat yang lebih siap bersaing di tingkat internasional.